Algebraic reconstruction technique for parallel imaging reconstruction of undersampled radial data: Application to cardiac cine - Li, Shu; Chan, Cheong; Stockmann, Jason P.; Tagare, Hemant; Adluru, Ganesh; Tam, Leo K.; Galiana, Gigi; Constable, R. Todd; Kozerke, Sebastian; Peters, Dana C. (Magnetic resonance in medicine, 2015)
Purpose To investigate algebraic reconstruction technique (ART) for parallel imaging reconstruction of radial data, applied to accelerated cardiac cine. Methods A graphics processing unit (GPU)‐accelerated ART reconstruction was implemented and applied to simulations, point spread functions and in 12 subjects imaged with radial cardiac cine acquisitions. Cine images were reconstructed with radial ART at multiple undersampling levels (192 Nr × Np = 96 to 16). Images were qualitatively and quantitatively analyzed for sharpness and artifacts, and compared to filtered back‐projection, and conjugate gradient SENSE. Results Radial ART provided reduced artifacts and mainly preserved spatial resolution, for both simulations and in vivo data. Artifacts were qualitatively and quantitatively less with ART than filtered back‐projection using 48, 32, and 24 Np, although filtered back‐projection provided quantitatively sharper images at undersampling levels of 48‐24 Np (all P < 0.05). Use of undersampled radial data for generating auto‐calibrated coil‐sensitivity profiles resulted in slightly reduced quality. ART was comparable to conjugate gradient SENSE. GPU‐acceleration increased ART reconstruction speed 15‐fold, with little impact on the images. Conclusion GPU‐accelerated ART is an alternative approach to image reconstruction for parallel radial MR imaging, providing reduced artifacts while mainly maintaining sharpness compared to filtered back‐projection, as shown by its first application in cardiac studies. Magn Reson Med 73:1643–1653, 2015. © 2014 Wiley Periodicals, Inc.